IMPLIKASI AUDIT PASCA KLAIM BPJS KESEHATAN TERHADAP KERUGIAN RUMAH SAKIT DALAM PERSPEKTIF AKUNTABILITAS DAN PRINSIP KEADILAN (STUDI PADA RSU GRANDMED) - Redyanto Sidi; Felix Kasim; Basyariah Lubis; Novita Br Ginting; Sri Melda Br Bangun (Universitas Labuhanbatu, 2026)
Post-claim audits conducted by BPJS Kesehatan serve as a supervisory mechanism to ensure accountability in the management of the National Health Insurance (JKN) funds. However, audit practices that result in claim corrections or deductions may cause financial losses to hospitals and raise concerns regarding procedural and distributive justice. This study aims to analyze the implications of post-claim audits on hospital financial losses from the perspective of accountability and the principles of justice at RSU Grandmed. This research employed a mixed-method approach with a cross-sectional design involving 97 respondents selected through purposive sampling. Quantitative data were analyzed using multiple linear regression, examining variables such as transparency of the claim process, auditor accountability, tariff adequacy, timeliness of payment, and allocation of claim funds. The findings indicate that, partially, transparency of the claim process, tariff adequacy, timeliness of payment, and allocation of claim funds significantly influence the hospital’s financial condition, while auditor accountability was not significant in the bivariate analysis. However, simultaneously all variables demonstrated a significant effect on hospital financial losses and financial sustainability (R² = 0.693). These findings demonstrate that post-claim audits are not merely administrative mechanisms but have direct implications for hospital financial stability. Therefore, audit mechanisms must be implemented in a transparent, consistent, objective, and justice-oriented manner to maintain a balance between public accountability and the sustainability of health service delivery.Keywords: Indonesia Health Social Security Agency; post-claim audit; accountability; principles of justice; hospital financial loss.